1978
DOI: 10.1042/bj1750239
|View full text |Cite
|
Sign up to set email alerts
|

The reactions of Pseudomonas cytochrome c-551 oxidase with potassium cyanide

Abstract: The binding of cyanide to both oxidized and ascorbate-reduced forms of Pseudomonas cytochrome c-551 oxidase was investigated. Spectral studies on the oxidized enzyme and its apoprotein showed that the ligand can bind to both the c and d, haem components of the molecule, and kinetic observations indicated that both chromophores reacted, under a variety of conditions, with very similar rates. Cyanide combination velocities were dependent on ligand concentration, and increasing the pH also accelerated the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 21 publications
6
24
0
Order By: Relevance
“…The 3D structure of the cyanide derivative of reduced P. pantotrophus NIR (23) shows that the two His and the Tyr in the active site are within H-bonding distance of cyanide, suggesting that a positive electrostatic potential in the pocket is essential for stabilization of the bound anion. An unusually high positive charge density has also been found in the heme pocket of the Escherichia coli sulfite reductase, an enzyme capable of binding both sulfite and nitrite with high affinity, catalyzing their reduction to sulfide and ammonia, respectively (26). The unique role of His-369 in stabilizing the enzyme-substrate complex, although unexpected, seems to be in agreement with the structural data shown in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The 3D structure of the cyanide derivative of reduced P. pantotrophus NIR (23) shows that the two His and the Tyr in the active site are within H-bonding distance of cyanide, suggesting that a positive electrostatic potential in the pocket is essential for stabilization of the bound anion. An unusually high positive charge density has also been found in the heme pocket of the Escherichia coli sulfite reductase, an enzyme capable of binding both sulfite and nitrite with high affinity, catalyzing their reduction to sulfide and ammonia, respectively (26). The unique role of His-369 in stabilizing the enzyme-substrate complex, although unexpected, seems to be in agreement with the structural data shown in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The high redox potential is consistent with the ability of ascorbate to reduce this enzyme. When P. ueruginosu cytochrome cd, is in the ferric state, both the c and dl haern can bind cyanide (Barber et al, 1978). Cyanide binding to haem c occurs by displacement of the methionine axial ligand and an interaction between the c haem and the dl hacm is indicated by a small change in the EPR spectrum of the c haem on the binding of cyanide to haem dl (Suthcrland et al, 1986).…”
Section: Denitrifying Enzymesmentioning
confidence: 99%
“…MCD studies of the cyanide derivative showed d, to be low-spin (Walsh et al, 1979). Carbon monoxide and cyanide inhibit the oxygen reductase activity of this enzyme, but only cyanide appears to inhibit the nitrite reductase activity (Barber et al, 1978;Parr et al, 1974). Thc reaction of cytochrome cd, nitrite reductase with CO has bccn studied by static titration, stopped-flow and flash photolysis ( P a r et al, 1975).…”
Section: Denitrifying Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44][45][46][47][48][49] Many date from the days when the enzyme was referred to as "bacterial cytochrome oxidase", because of its ability to reduce O 2 to water (albeit much more slowly than mammalian cytochrome c oxidase) and the presence of four electron acceptor groups per dimer. These studies were aimed at exploring the relationship between the bacterial and mammalian cytochrome oxidases.…”
Section: A Heme CD 1 -Containing Nitrite Reductasesmentioning
confidence: 99%